Commercialisation activities in biotechnology research related among academicians in Malaysia - Yaacob, Noorulsadiqin Azbiya; Md Rasli, Amran; Amat Senin, Aslan; Othman, Siti Norezam (2010)
The paper analyses the perceptions of 79 academic researchers regarding their involvement in ommercialisation activities of their research activities in a research university environment base on a questionnaire. Factor analysis and reliability tests were conducted to identify dimensions of commercialisation activities and to determine statistical reliability of the dimensions. Subsequently, Kruskal Wallis tests were conducted to examine whether perceptions on commercialisation activities results differ based on the demographic background of the researchers.The findings of this study reveal perceptions on the commercialisation dimensions are ranked highest for researchers who are professors with more than 10 years research experience while having high level of experience as university administrators.